Outcomes of Early Versus Late Reversal in Patients with Loop Ileostomy Formation Secondary to Typhoid Perforation - Hassan Shahab, Muhammad Sheheryar Hussain, Radeyah Waseem, Komal Faheem, Sumbla Salman, Bushra Jawaid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess if there is significant risk associated with early reversal of stomas (less than 6 weeks) when compared to a delayed closure in the setting of a Tertiary Care Hospital in Karachi. Study design: Observational longitudinal study Study place and duration: Dow University, Karachi 6 months 1st April 2022 till 1st September 2022 Methods: Pre- and post-operative data were collected for 50 patients assigned to each group respectively. The parameters assessed were the American Society of Anesthesiologists (ASA) grade, Surgery duration, Post-operative and Overall Hospital Stay, Surgical and Medical complications and day of occurrence, Clavein-Dindo Classification, and mortality. Results: Significant variance in ASA Grade was noted between the two groups, P-Value=0.005 with a lower grade observed in patients who underwent early closure. The post-operative and total hospital stay showed significant variation, with P-values of 0.011 and 0.011, respectively for both outcomes. The incidence of post-operative complications was also significant with p-value=0.004. The median day at which post-operative complication occurred was 4.5 vs 3 days with a significant p-value of 0.038. Conclusions: Late closure is associated with a significantly higher risk of complications and a resultant greater length of hospital stay. Keywords: Ileostomy, stoma, intestinal perforation, and typhoid.